2015
DOI: 10.1111/jpn.12400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arginine and threonine administered in ovo on digestive organ developments and subsequent growth performance of broiler chickens

Abstract: This trial was conducted to investigate the effect of arginine (Arg), threonine (Thr) and Arg + Thr administered in ovo on growth performance, digestive organs and intestinal morphology in broiler chickens. On day 14 of incubation, 400 fertile eggs were randomly allotted to five experimental treatments through injection in the amniotic fluid including: (i) control (none injected), (ii) sham (0.5 ml of 0.5% saline), (iii) Arg (35 mg/egg), (iv) Thr (25 mg/egg) and (v) Arg + Thr (35 + 25 mg/egg). After hatching, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
5
19
0
1
Order By: Relevance
“…Results of this study showed that, IOF of Arg solution elevated the development of liver, pancreas, proventriculus and gizzard both in chick embryos and in broilers during the first week post‐hatch as well as the intestine (unpublished data). In agreement with the results of the current work, Tahmasebi and Toghyani () reported that IOF of Arg increased the weights of liver, proventriculus, duodenum and ileum of 11‐day‐old broilers and the weights of gizzard, duodenum and jejunum of 42‐day‐old broilers compared with the non‐injected control. Al‐Daraji et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results of this study showed that, IOF of Arg solution elevated the development of liver, pancreas, proventriculus and gizzard both in chick embryos and in broilers during the first week post‐hatch as well as the intestine (unpublished data). In agreement with the results of the current work, Tahmasebi and Toghyani () reported that IOF of Arg increased the weights of liver, proventriculus, duodenum and ileum of 11‐day‐old broilers and the weights of gizzard, duodenum and jejunum of 42‐day‐old broilers compared with the non‐injected control. Al‐Daraji et al.…”
Section: Discussionsupporting
confidence: 92%
“…This was clearly indicated by the increase in YSW not only at 19 days of incubation but also at 1‐ and 3‐day‐old post‐hatch broilers (Table ). Besides, some other authors explained that the increasing of BWG by IOF of Arg might be ascribed to the alleviation AA demand of chicks during embryonic phase, the stimulation of greater protein synthesis and lower protein degradation (Al‐Daraji, Al‐Mashadani, Al‐Hayani, Al‐Hassani, & Mirza, ; Tahmasebi & Toghyani, ).…”
Section: Discussionmentioning
confidence: 99%
“…All the eggs were candled on day 14 of embryotic age, the injection points were located and shell surface was disinfected. Four hundred fertile eggs were allotted to 5 treatments of 80 eggs with 4 replicates (20 eggs per replicate) including: control (none injected); sham group (0.5 ml of 0.5% saline); 35 mg Arg (L-arginine, #A5006; Sigma-Aldrich Inc., St. Louis, MO, USA) dissolved in 0.5% saline (0.5 ml/egg); 25 mg Thr (L-Threonine, #T 8625; Sigma-Aldrich Inc., St. Louis, MO, USA) dissolved in 0.5% saline (0.5 ml/ egg); 35 mg Arg þ25 mg Thr dissolved in 0.5% saline (0.5 ml/egg) which was confirmed by the preliminary experiment in (Tahmasebi and Toghyani 2016). Moreover, saline concentration is based on the concentration applied in the work of Uni et al (2005).…”
Section: Experimental Treatments and Injection Proceduressupporting
confidence: 52%
“…72 Injection of arginine (35 mg per egg) and threonine (25 mg per egg) and their mixture into amnion improved feed efficiency and post-hatch growth rate of broilers. 62 In ovo feeding of arginine improved the weight of chick embryos at the 19th day of incubation and the weight gain of chicks during the first week of age, as well as the weights of pancreas, liver, gizzard, and proventriculus; arginine also enhanced the levels of glucagon-like peptide 2, duodenal ghrelin, and vasoactive intestinal peptide, in addition to the activities of duodenum mucosal enzymes maltase, alkaline phosphatase, inducible nitric oxide synthase, and sucrase of 7-day-old post-hatch broilers in comparison with control. 45 In ovo injection of glutamine and diamond nanoparticles was beneficial in accelerating the growth and maturation of muscles, especially pectoral muscles and breast muscles in chicken embryo.…”
Section: Amino Acidsmentioning
confidence: 99%